THE DEVELOPMENT OF MEDICAL EDUCATION AND TRAINING IN TELANGANA: HISTORICAL PROGRESS AND CONTEMPORARY CHALLENGES (1947-2021) - Anjaneyulu, L (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the development of medical education and training in Telangana from 1947 to 2021, tracing its historical evolution and analyzing contemporary challenges. Over the decades, Telangana has witnessed significant progress in establishing medical institutions and expanding training programs, contributing to the growth of a robust healthcare workforce. The initial post-independence period focused on creating foundational medical colleges and addressing the shortage of healthcare professionals. The 1970s and 1980s saw the expansion of medical education, with an increase in the number of institutions and the introduction of specialized training programs. In recent decades, Telangana has continued to enhance its medical education infrastructure, incorporating advanced technologies and updated curricula to meet global standards. This study explores these challenges and provides a comprehensive analysis of the policies and initiatives aimed at addressing them. By examining the historical trajectory and current state of medical education in Telangana, the research offers insights into the factors that have shaped its development and the areas that require further attention to ensure the production of competent and skilled healthcare professionals in the region.